Japan - Kingston, Jeff 1957- (Polity, 2019)
"In this compact and lively book, Jeff Kingston - one of the most lucid analysts of Japan today - takes readers on a fascinating journey through this country's contemporary history, exploring the key developments and forces, both at home and abroad, that are shaping Japan in the 21st century"--Provided by publisher.